Cricket Radio : tuning in the night-singing insects - Himmelman, John (Belknap Press of Harvard University Press, 2011)
At a time when night-singing insects have slipped beyond our notice-indeed, are more likely to be heard as NatureSounds than in a backyard-John Himmelman seeks to reconnect us to creatures whose songs form a part of our own natural history. On warm summer evenings, night-singing insects produce a whirring, chirping soundscape-a calming aural tapestry celebrated by poets and naturalists for millennia. But "cricket radio" is not broadcast for the easy-listening pleasure of humans. The nocturnal songs of insects are lures and warnings, full of risks and rewards for these tiny competitive performers. What moves crickets and katydids to sing, how they produce their distinctive sounds, how they hear the songs of others, and how they vary cadence, volume, and pitch to attract potential mates, warn off competitors, and evade predators is part of the engaging story Cricket Radio tells. Himmelman's narrative weaves together his personal experiences as an amateur naturalist in search of crickets and katydids with the stories of scientists who study these insects professionally. He also offers instructions for bringing a few of the little singers into our homes and gardens. We can, Himmelman suggests, be reawakened to these night songs that have meant so much to the human psyche. The online insect calls that accompany this colorfully illustrated narrative provide a bridge of sound to our past and to our vital connection with other species